(untitled) (Northern University Journal of Law, 2015)
This article emphasizes on the implication of the doctrine of capital maintenance which means the capital of a company needs to be kept intact for there is a contribution of the creditors and retaining the capital is normally expected to guarantee repayment to the creditors. Any reduction of capital can diminish the liability of members and consequently the position of the creditors can be vulnerable. Therefore, an attempt has been made by this study to reveal the origin, objective and application of the doctrine of capital maintenance to find out a way by which we can save the interest of the creditors as well as satisfy the needs of the modern business. Northern University Journal of Law Vol.IV 2013; p.47-55